This repository ccontains assignments, lecture notes, books and other resources for the course COL778/864 offered by Prof. Rohan Paul in the semester 2302 at IITD. The course deals with the algorithmic aspects of intelligent robotics and more generally autonomous systems.
-
State Representation :
-
Bayes Filtering Algorithm :
-
Read Bishop Chapter 8 to learn about Graphical Models
-
Can be broken down into two steps
-
Action update step
$p(x_t | z_1,....z_{t-1}, u_1,....u_t)$
$p(x_t | z_1,....z_{t-1}, u_1,....u_t) = \int_{x_{t-1}}p(x_t | z_1,....z_{t-1}, u_1,....u_t, x_{t-1})p(x_{t-1} | z_1,....z_{t-1},u_1,....u_t)dx_{t-1}$
Now,$p(x_t | z_1,....z_{t-1}, u_1,....u_t, x_{t-1}) = p(x_t | x_{t-1}, u_t)$ and$p(x_{t-1} | z_1,....z_{t-1},u_1,....u_t) = Bel(x_{t-1})$ $\therefore p(x_t | z_1,....z_{t-1}, u_1,....u_t) = \int_{x_{t-1}}p(x_t | x_{t-1}, u_t)Bel(x_{t-1})dx_{t-1}$
or,$\overline{Bel}(X_t) = \int_{x_{t-1}}p(x_t | x_{t-1}, u_t)Bel(x_{t-1})dx_{t-1}$
-
Measurement update step
$p(x_t | z_1,....z_{t}, u_1,....u_t)$
$p(x_t | z_1,....z_{t}, u_1,....u_t) = \eta * p(z_t | x_t,z_1,....z_{t-1}, u_1,....u_t) * p(x_t |z_1,....z_{t-1}, u_1,....u_t)$ Now,
$p(z_t | x_t,z_1,....z_{t-1}, u_1,....u_t) = p(z_t | x_t)$
$\therefore Bel(x_t) = \eta * p(z_t | x_t) * \overline{Bel}(x_t)$
-
-
-
State Estimation using Kalman Filters :
-
Read about Conditioned Joint Gaussian PDFs here.
-
Calculation of co-variance matrix
$\sum_{X_tX_{t+1}}$ used in derivation of the action update equations
$\sum_{X_{t+1}X_t}$ =$\mathbb{E}[(X_{t+1} - \mu_{X_{t+1}})(X_t - \mu_{X_t})^T]$ $\sum_{X_{t+1}X_t}$ =$\mathbb{E}[(X_{t+1} - A_t\mu_t - B_t\mu_t)(X_t - \mu_t)^T]$ $\sum_{X_{t+1}X_t}$ =$\mathbb{E}[(A_tX_t - A_t\mu_t + \epsilon_t)(X_t - \mu_t)^T]$ $\sum_{X_{t+1}X_t}$ =$\mathbb{E}[(A_tX_t - A_t\mu_t + \epsilon_t)(X_t^T - \mu_t^T)]$ $\sum_{X_{t+1}X_t}$ =$\mathbb{E}[A_tX_tX_t^T - A_t\mu_tX_t^T + \epsilon_tX_t - A_tX_t\mu_t^T + A_t\mu_t\mu_t^T - \epsilon_t\mu_t^T]$ Since
$\epsilon_t$ is an independent zero-mean random variable, all terms with$\epsilon_t$ go to 0$\sum_{X_{t+1}X_t}$ =$\mathbb{E}[A_tX_tX_t^T - 2 * A_t\mu_tX_t^T + A_t\mu_t\mu_t^T]$ $\sum_{X_{t+1}X_t}$ =$A_t\mathbb{E}[X_tX_t^T] - A_t\mu_t\mu_t^T$ $\sum_{X_{t+1}X_t}$ =$A_t(\mathbb{E}[X_tX_t^T] - \mathbb{E}[X_t]\mathbb{E}[X_t]^T)$ $\sum_{X_{t+1}X_t}$ =$A_t\sum_{t|0:t}$
-
-
MDPs :